Ácaros (Acari, Arachnida) associados a euforbiáceas nativas em áreas de cultivo de seringueiras (Hevea brasiliensis Muell. Arg., Euphorbiaceae) na região noroeste do estado de São Paulo, Brasil - Feres, Reinaldo J.F. [UNESP]; Nunes, Maria Andreia [UNESP] (Sociedade Brasileira de Zoologia, 2001)
This paper reports twenty mite species belonging to eighteen genera in nine families, associated with three species of euphorbiaceous weed species: Chamaesyce hirta (Linnaeus) Millsp., Euphorbia heterophylla L. and Phyllanthus tenellus (Muell. Arg.) Roxb., in three different monoculture areas of Hevea brasiliensis. The largest richness of mite species was observed on C. hirta, with nine species. The most abundant species were Pronematus sp. and Polyphagotarsonemus latus (Banks, 1904), collected on C. hirta and E. heterophylla.
Mites (Acari, Arachnida) associated with weed Euphorbiaceae in monoculture planting of the amazonian rubber tree (Hevea brasiliensis Muell. Arg., Euphorbiaceae) in Northwestern São Paulo State, Brazil
Keywords: Acari; Mites; weed Euphorbiaceae; Biodiversity; Brazil